Single frequency erbium doped fiber laser with a highly doped erbium-doped fiber - Lokman, A.; Hamzah, A.; Huri, N.A.D.; Arof, Hamzah; Ahmad, F.; Ahmad, Harith; Harun, Sulaiman Wadi (INOE, 2010)
A single frequency Erbium-doped fiber laser (EDFL) operating at 1552.5 nm has been demonstrated by using a 2 m long of newly developed Zirconia-based Erbium-doped fiber (Zr-EDF) as a gain medium. The Zr-EDF is fabricated by combining Zr and Al to achieve the maximum Erbium ion concentration of 4320 ppm wt. By using a fiber Bragg grating (FBG) in a ring configuration, a laser which operates at 1552.5 nm with signal to noise ratio of 60 dB is generated. The linewidth of the EDFL is measured to be approximately 95 MHz using a heterodyne technique.